PERILAKU CYBERBULLYING PADA MEDIA SOSIAL TIKTOK (ANALISIS ISI KUALITATIF PERILAKU CYBERBULLYING DI KOLOM KOMENTAR DALAM AKUN TIKTOK @OFP24) - Utami, Ayu Wulandari; Arianto, Irwan Dwi (Linimasa : Jurnal Ilmu Komunikasi, 2024)
Advances in Internet technology have a positive impact on users in expanding social networks by using social networking or called social media. The negative effects of social media are online fraud, theft, identity abuse, pornography, cyberbullying and others. The purpose of this study is to know how cyberbullying is done in the comments column of the TikTok account @ofp24 at the postings in September - October 2023. In the study, CMC (computer mediated communication) theory is used by using a qualitative approach for miles&huberman's analysis of content. The collection of data in this research was by observation and documentation.The results of this research were the discovery of three types of cyberbullying that occurred in the comments column of the TikTok account @ofp24 in September-October 2023, namely flaming, harassment and denigration. Keywords: Social Media, Cyberbullying, TikTok